NONLINEAR MODELING USING CENTRAL COMPOSITION PLAN FOR FORECASTING OF CHARACTERISTICS OF RAW SAND BLEND - M. A. Sajkov; V. M. Karpenko; N. P. Dragun; E. V. Filipenko (Литьë и металлургия)
Using of such statistical instruments as experiment planning and methodology of response surface in order to receive correlation between input-output variable quantities in sandy-argillaceous blends is shown.